Species diversity of Tricholoma (Agaricales, Tricholomataceae) from Shanxi Province of northern China with the description of four new species - Ning Mao; Jia-Jia Yang; Yu-Xin Zhang; Ting Li; Li Fan (MycoKeys)
Species of Tricholoma are of great economic and ecological value. There are many studies on Tricholoma worldwide, but the areas investigated are generally North America and Europe. There is limited knowledge about Tricholoma in China. In this study, 21 species of Tricholoma were confirmed in Shanxi Province based on morphological and molecular phylogenetic analyses. These species are located in eight sections, viz. sect. Atrosquamosa, sect. Genuina, sect. Lasciva, sect. Matsutake, sect. Pardinicuti, sect. Rigida, sect. Terrea and sect. Tricholoma. Of these, four species are described as new to science: T. flavoviride, T. fumeobrunneum, T. parafulvum, and T. viscidum.